2018
DOI: 10.5152/turkpediatriars.2018.5749
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of frequent relapsing and steroid-dependent nephrotic syndrome in children

Abstract: Steroide duyarlı nefrotik sendromu olan çocuklarda sık relapsların ve steroid bağımlılığının öngördürücülerini belirlemek amaçlandı. Gereç ve Yöntemler: Üçüncül bir merkezde 2003 ile 2015 yılları arasında steroide duyarlı nefrotik sendrom tanısı ile nefroloji kliniğine kaydedilmiş olan ve hastalık başlangıcından sonra en az bir yıl izlenen altı ay ile 18 yaş arasındaki bütün çocuklar çalışmaya alınmıştır. Bulgular: Hastalık başlangıcından itibaren en az bir yıl izlenmiş olan steroide duyarlı nefrotik sendrom t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
9
1
Order By: Relevance
“…Sarkeret al, [13] showed that ages less than 5 years are more prone to have FR compared to those older than 5 years. Dakshayaniet al, [14] followed up 227 Turkish children one year after the first episode and reported that FR had significantly associated with lower age at onset. An almost a similar result was reported by Mishra et al, [15] among Indian children in which the authors found that the risk of FR was 3-time greater in 1-3 year-age compared to children over 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Sarkeret al, [13] showed that ages less than 5 years are more prone to have FR compared to those older than 5 years. Dakshayaniet al, [14] followed up 227 Turkish children one year after the first episode and reported that FR had significantly associated with lower age at onset. An almost a similar result was reported by Mishra et al, [15] among Indian children in which the authors found that the risk of FR was 3-time greater in 1-3 year-age compared to children over 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory tract infections (RTI) are common complications of PNS (2,3). Infections not only reduce the efficacy of glucocorticoid treatment but also lead to prolonged duration and frequent recurrence in PNS (4,5). The pathogenic spectrum and their susceptibility to antibiotics in RTI change over time, which increases the difficulty of anti-infection treatment.…”
Section: Introductionmentioning
confidence: 99%
“…edema, and various complications especially hypovolemia, infection and thrombosis (1) (2) . It is caused by increased permeability through the damaged basement membrane in the renal glomerulus (3) .…”
mentioning
confidence: 99%
“…Remission: Urine albumin nil or trace (or proteinuria less than 4 mg/m/h) for 3 consecutive early morning specimens. Relapse: Urine albumin 3+ or 4+ (or proteinuria more than 40 mg/m/h) for 3 consecutive early morning specimens having been in remission previously (2) .…”
mentioning
confidence: 99%
See 1 more Smart Citation